IMPLEMENTASI METODE HABITUASI DALAM MEMBENTUK KARAKTER DISIPLIN DAN TANGGUNG JAWAB DI SD MUHAMMADIYAH 1 PAITON - Mustika, Diah; Kasdriyanto, Didit Yuliana; Hattarina, Shofia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Character education is an essential aspect of elementary school education, particularly in developing students’ discipline and responsibility. However, problems related to low discipline and responsibility among students are still frequently found in the school environment. Therefore, an effective method is needed to build positive habits and behaviors in students. One of the methods that can be applied is the habituation method through continuous and consistent daily activities. This study aims to describe the implementation of the habituation method in shaping students’ disciplinary and responsible character at SD Muhammadiyah 1 Paiton and to identify the supporting and inhibiting factors in its implementation. This research used a qualitative descriptive method with a case study approach. Data collection techniques were carried out through observation, interviews, and documentation. The results showed that the implementation of the habituation method at SD Muhammadiyah 1 Paiton was conducted through various routine activities such as morning assemblies, collective prayers, queue culture, classroom cleaning duties, maintaining school cleanliness, and completing assignments on time. The habituation method was proven to help students develop disciplinary behavior in obeying school rules and improve their sense of responsibility toward assigned tasks and obligations. Supporting factors included teacher cooperation, school support, and a conducive learning environment, while inhibiting factors included students’ lack of awareness and external environmental influences. Therefore, the habituation method is considered effective in shaping students’ disciplinary and responsible character when implemented consistently and continuously in elementary schools.